FINANCIAL FEASIBILITY ANALYSIS OF CHILI (Capsicum frutescens L.) FARMING IN THE MANEBALA FARMERS GROUP - Berlita Yohana Berum; Frengky Lambu Apu; Toar Daniel Malingkas (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Capsicum frutescens L is one of the horticultural commodities that has economic value and has the potential to increase farmers' income. This study aims to determine the financial feasibility of this commoditing farming in at Manebala Farmers Group in Kabuna Village, Kakuluk Mesak District, Belu Regency. The method used in this study is a quantitative descriptive method. Data was obtained through interviews, observation, and documentation. Data analysis was carried out by calculating production costs, revenue, income, R/C Ratio, B/C Ratio, as well as the Break Even Point (BEP). The results showed that the total production cost of bird's eye chili farming was IDR 53,175,000 per year or IDR 7,623,700 per planting season. The total revenue obtained was IDR 172,640,000 per year and IDR 86,320,000 per planting season, while the income was IDR 119,465,000 per year and IDR 59,732,500 per planting season. The R/C Ratio was 3.25 per year and 1.62 per planting season, while the B/C Ratio value. amounting to 2.25 per year and 1.12 per planting season. The production BEP was 1,329 kg per year and 664.69 kg per planting season, and the price BEP was Rp.12,320/kg per year and Rp.6,160.22/kg per planting season. Based on the research results, chili farming at the Manebala Farmers Group is considered feasible and profitable to cultivate and develop.